Estudo sobre o comportamento de apetência de diferentes estágios do carrapato Amblyomma cajennense (Acari: Ixoidae) - ASSAL, Flávio Ezzeddine El (2008)
This paper evaluates the behavior of appetite expressed in different stages of the ticks Amblyomma cajennense testing the hypothesis that nymphs and adults of this species have strategy of game play while the larvae ambush. To this end, through observations, we sought to describe and propose a classification of appetite expressed by these different stages comparing strategies appetite displayed by different instars of the species with the express adult Rhipicephalus sanguineus on the same environmental conditions. Experimentally, the expressions of these behaviors face of different stimuli (CO2, equine odor, shading, radiant heat, and the 'air control') were evaluated. For this, we collected ticks of the species in horses and dogs naturally infested Center for Zoonosis Control in Goiânia-GO, which were created in rabbits and multiplied in the vivarium of the Center for Veterinary Parasitology, Federal University of Goiás (CPV / UFG ). The ratings of the behaviors that occurred in a room of the Centre -CPV/UFG were held in a glass box with removable cover, having a dozen plastic rods for the expression of search strategies. This glass chamber showed temperature conditions (25 º C + / -3 ° C), relative humidity (80% <RH <98%) and light (12 hours light / 12 hours of darkness) known and standard in all tests. In this environment were the observation sessions, each 40 minutes long, starting when after a period of 29 hours of environment of the ticks in the study. At each session, we evaluated a group of ten ticks (the same age and species) by the methodology - scan 'scan sampling' - every minute, recording the positions of the individuals on appropriate sheet. For each stimulus were evaluated ten groups of ten individuals. For registration were considered four possible attitudes: complete inactivity (first pair of legs retracted), and only motions of searching raising the first pair of legs; stopped or partial inactivity (first pair of legs exposed despite the immobility of the tick) and displacement by the glass box (walking). Possible locations were the twelve rods, base, walls and lid of the box. Was used factorial ANOVA to evaluation of results which, together with other elements derived from the observations, allowed the conclusion that under the conditions applied, larvae A.cajennense conduct ambush while nymphs and adults of this species are hunters of their potential hosts